ANALISIS KESULITAN MAHASISWA DALAM MENYELESAIKAN SOAL MATRIKS - Aminullah Aminullah (Universitas Mahasaraswati Mataram, 2020)
This study aims to describe the type and location of student difficulties in solving matrix problems. This research is a survey research with quantitative and qualitative approaches. The sample in this study were 13 students from the Civil Engineering Study Program at Mataram UNMAS Denpasar Campus. Retrieval of data using test instruments and analyzed using quantitative-qualitative analysis. The results of this study indicate that the type of student difficulties related to facts is 13.64%, the difficulty in the concept is 31.31%, the difficulty in principle is 28.79% and the difficulty in the skill is 26.36%. While the location of students' difficulties on points is known to be 12.52%, points were asked at 12.52%, formula points were 4.46%, systemic completion points were 15.78%, inter-concept links were 11.15%, relationship points facts - concepts 12.35%, mathematical basic operating points 12.41% and final answer points 16.81%. The type and location of the most dominant difficulties students have in solving matrix problems lies in understanding the concepts and final answers of students.